Cold storage networks powered with renewable energy - Ambler, Kate; Bloem, Jeffrey R.; McNamara, Brian (International Food Policy Research Institute, 2025)
Cold-storage networks are a key technology that can address the nutritional and environmental costs of food loss and waste within many low- and middle-income countries. In addition to coordination challenges and network externalities that complicate efforts to scale these networks, they require large amounts of energy, carrying the potential of environmental damage via carbon emissions. Thus, using renewable energy sources to power cold-storage networks holds the potential to reduce the environmental damage associated with food loss and meet the increased demand for energy.